Global Taiwanese : Asian skilled labour migrants in a changing world - Moore, Fiona (University of Toronto Press, 2021)
"In Global Taiwanese, Fiona Moore explores the different ways in which Taiwanese expatriates living in London and Toronto, along with globally networked professionals in Taipei, use their shared Taiwanese identities to construct and maintain global and local networks. Based on a three-year-long ethnographic study that incorporates interviews with people from diverse backgrounds, generations and histories, Global Taiwanese explores what their different experiences tell us about migration in "tolerant" and "hostile" regimes. Global Taiwanese considers the implications of the Taiwanese case for understanding the processes by which transnational professionals more generally use ethnic identity in their business and personal lives. As people become increasingly mobile, ethnic identity becomes more important as a means of negotiating transnational encounters; however, at the same time, the opportunities it offers are rooted in local cultural practices, requiring professionals and other migrants to develop complex social strategies that link and cross the global and local levels. With rich ethnographic detail, this book contributes to the understanding of the migrant experience and how it varies from location to location, how migration more generally changes in response to wider socioeconomic factors, and, finally, of the specific case of Taiwan and how the distinctive nature of its diaspora emerges through wider discourses of Chineseness and pan-Asian identity."--